Strategi Kemitraan di PT. DIF Nusantra dan Bali Fresh Female Farmers Group (BFFFG) di Desa Kedisan, Kecamatan Kintamani, Kabupaten Bangli, Bali. - Anggraini, Lina; Yusdiarti, Arti; Nahraeni, Wini (JURNAL AGRIBISAINS, 2017)
This study was aimed to identify internal and external factors in BFFFG, develope alternative strategies to conduct SWOT analysis. The study was done in Kedisan Village, KintamaniDistrict, Bangli Regency, Bali. Data were collected for 4 months from 12 June to 2 October 2006 through direct interview by using open questionnaires and discussion. IFE, EFE, andSWOT analysis. Based on the results of SWOT analysis, strategies were developed. These included introducing ”Bali Fresh” products to areas outside Bali island, maintaining thecompany’s marketing strategies, and utilizing abandoned vegetables to open new opportunity for the company. Several recommendations given were : the establishment of kindergarten for children of partner farmers, adding more young labors, transparency on harvested product price. For PT DIF Nusantara, it was recommended that new consumers be sought in order to reduce wasted vegetables.Keywords: Strategy, Working time allocation, SWOT